Ozone corrosion-resistant high-strength tube and method of manufacturing the same
Patent Information
- Application Number
- KR1020247019435
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-01-13
- Filing Date
- 2023-01-09
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2043-01-09
Smart Images

Figure 112024062689753-PCT00005_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a tube and a method for manufacturing the same, and in particular to an ozone corrosion-resistant high-strength tube and a method for manufacturing the same. Background Technology
[0002] As is well known, ozone is commonly used in current water supply facilities to ensure water quality by disinfecting and sterilizing water sources. In practical applications, the pipeline between the ozone generator and the ozone dosing device in a water supply facility typically comes into direct contact with ozone gas. The water discharge pipes of the pre-ozone contact tank and the ozone contact tank also come into contact with water in which ozone has been dissolved. Unless these equipment and pipelines are specially treated, they are highly susceptible to ozone corrosion. Therefore, to minimize corrosion caused by ozone, current equipment and pipelines are generally produced and manufactured using carbon steel and 316 stainless steel materials.
[0003] However, compared to carbon steel materials, 316 stainless steel structures have lower strength and require greater thickness under the same operating conditions, leading to an increase in the amount of material used. At the same time, welding and machining operations using 316 stainless steel are more difficult. Furthermore, 316 stainless steel itself contains higher levels of precious metal elements such as Cr, Ni, and Mo, which increases operating costs during production, manufacturing, and installation. When using 316L stainless steel in conventional configurations, localized material corrosion occurs primarily in ozone environments due to a lack of comprehensive corrosion resistance.
[0004] Therefore, carbon steel tubes are generally manufactured from carbon steel and can be used as pre-ozone contact tanks and as water discharge pipes behind the valves of these tanks; the water transported through these pipelines contains a small amount of residual ozone. To improve the corrosion resistance of the pipeline inner walls, measures are typically adopted to apply a special ozone-resistant fluorocarbon coating to the inner walls. However, due to issues such as damage and peeling of the coating on the pipeline inner walls, carbon steel tubes continue to corrode due to ozone during long-term use and operation, leading to water pollution, and even pipeline leaks and explosions.
[0005] Accordingly, the present invention aims to provide a new tube that possesses excellent ozone corrosion resistance while also exhibiting superior mechanical properties and economic efficiency, taking into account the problems and defects of the conventional technology described above, thereby seeking to obtain significant economic and social benefits. The problem to be solved
[0006] One of the objectives of the present invention is to provide a tube that not only has excellent ozone corrosion resistance but also excellent mechanical properties and high economic efficiency, which solves the essential problems of 316 stainless steel or carbon steel used in water supply facilities in ozone-corrosive media environments, meets the increasing demands for corrosion resistance and mechanical properties for pipelines and equipment used in water supply facilities in ozone-corrosive media environments, significantly improves the applicability, safety, and durability of such pipelines and equipment, and provides significant economic and social benefits by preventing secondary contamination of water. means of solving the problem
[0007] To achieve the above objective, the present invention provides a tube, wherein the tube has a corrosion-resistant layer and a base layer in the thickness direction, the corrosion-resistant layer is located at least on the inner wall of the tube, and in addition to Fe and unavoidable impurities, the corrosion-resistant layer further contains the following chemical elements in a mass percentage:
[0008] 0 <C≤0.08%;
[0009] 0 <Si≤0.75%;
[0010] 0 <Mn≤2.0%;
[0011] Ni: 10.00-14.00%;
[0012] Cr: 16.00-18.00%;
[0013] Mo: 2.00-3.00%; and
[0014] N: 0.02-0.20%;
[0015] Here, Cr, Mo, and N satisfy the following inequality: Cr + 3.3 χ²Mo + 16 χ²N ≥ 25%.
[0016] Preferably, the anti-corrosion layer comprises the following chemical elements in mass percentage:
[0017] 0 <C≤0.08%;
[0018] 0 <Si≤0.75%;
[0019] 0 <Mn≤2.0%;
[0020] Ni: 10.00-14.00%;
[0021] Cr: 16.00-18.00%;
[0022] Mo: 2.00-3.00%; and
[0023] N: 0.02-0.20%;
[0024] The remainder is Fe and inevitable impurities;
[0025] Here, Cr, Mo, and N satisfy the following inequality: Cr + 3.3 χ²Mo + 16 χ²N ≥ 25%.
[0026] To ensure the ozone corrosion resistance of the tube, the ozone corrosion resistance of the anti-corrosion layer must first be ensured.
[0027] In current water supply facilities, the pipeline between the ozone generator and the ozone dosing device carries or comes into contact with 100% ozone gas as a medium. The pre-ozone contact tank, its flanges, blind sheets, discharge pipes, and other facilities carry or come into contact with water containing 1 mg / L to 3 mg / L of dissolved ozone as a medium, and said water contains up to 5 ppm of Cl - This may be included. The main corrosive medium is ozone, and the operating temperature is 0 to 40°C.
[0028] Based on the aforementioned operating conditions of pipelines and equipment used in water supply facilities in current ozone corrosion media environments, the inventors conducted extensive research on the chemical elemental composition of the corrosion-preventive layer and implemented an optimized design to ensure the ozone corrosion resistance of the corrosion-preventive layer.
[0029] In the present invention, the design principle of the chemical elements of the corrosion-preventing layer is as follows.
[0030] C: In the corrosion-preventing layer according to the present invention, C is a strong austenite-forming element that can replace nickel to some extent, promote austenite formation, stabilize the austenite structure, and simultaneously increase the strength of the stainless steel. However, it should be noted that the C content should not be too high. If the carbon content is too high, the bonding between carbon and chromium forms chromium-rich carbides at the grain boundaries, leading to intergranular corrosion. Therefore, to exert the beneficial effects of C, the mass percentage of C in the corrosion-preventing layer according to the present invention is 0 <C≤0.08%를 만족하도록 제어한다.
[0031] In some preferred embodiments, to obtain better technical effects, the mass percentage of C is preferably controlled between 0.005% and 0.030%.
[0032] Si: In the corrosion-preventing layer according to the present invention, since Si is mainly used for deoxidation in the smelting process, a certain amount of silicon is generally included. However, it should be noted that the Si content should not be too high. If the Si content is too high, the solubility of nitrogen decreases. Therefore, in the corrosion-preventing layer according to the present invention, the mass percentage of Si is 0 <Si≤0.75%를 만족하도록 제어한다.
[0033] In some preferred embodiments, to obtain better technical effects, the mass percentage of Si is preferably controlled between 0.3% and 0.6%, more preferably between 0.4% and 0.6%.
[0034] Mn: In the corrosion-preventing layer according to the present invention, Mn is a powerful austenite structure-stabilizing element and can increase the solubility of nitrogen in steel. However, manganese simultaneously has a negative effect on the corrosion resistance of austenitic stainless steel. Therefore, by balancing the beneficial and negative effects of Mn, the mass percentage of Mn in the corrosion-preventing layer according to the present invention is 0 <Mn≤2.0%를 만족하도록 제어한다.
[0035] In some preferred embodiments, to obtain better technical effects, the mass percentage of Mn is preferably controlled between 0.5% and 1.5%, more preferably between 1.10% and 1.25%.
[0036] Ni: In the corrosion-resistant layer according to the present invention, Ni is the most important element for forming and stabilizing the austenite phase, and adding an appropriate amount of Ni can ensure the formation of an austenite structure of steel at room temperature. However, nickel is expensive, and in order to ensure a relatively low cost, the mass percentage of Ni in the corrosion-resistant layer according to the present invention is controlled between 10.00% and 14.00%.
[0037] In some preferred embodiments, to obtain better technical effects, the mass percentage of Ni is preferably controlled between 12.00% and 14.00%.
[0038] Cr: In the corrosion-resistant layer according to the present invention, Cr is a guarantee for obtaining the stainlessness and corrosion resistance of stainless steel, and generally, the minimum chromium content for obtaining corrosion resistance is 10.5%. Since chromium is an element that significantly improves corrosion resistance, the chromium content of the steel of the present invention is controlled to 16.0% or more to ensure good corrosion resistance. However, chromium is a major ferrite-forming element, and if the chromium content is too high, it will be difficult to ensure an austenite structure in the cladding at room temperature. Therefore, in the corrosion-resistant layer according to the present invention, the mass percentage of Cr is controlled between 16.00% and 18.00%.
[0039] In some preferred embodiments, to obtain better technical effects, the mass percentage of Cr is preferably controlled between 16.50% and 17.50%.
[0040] Mo: In the corrosion-resistant layer according to the present invention, Mo is an important element for improving corrosion resistance, and its mechanism is to stabilize the passivation film and promote the concentration of chromium in the passivation film. Molybdenum can also exhibit a synergistic effect with nitrogen to further improve pitting corrosion resistance. Therefore, the main function of adding molybdenum is to improve corrosion resistance. It should be noted that the Mo content should not be too high. If the Molybdenum content is too high, the cost of the alloy will increase. To ensure a relatively low cost, the mass percentage of Mo in the corrosion-resistant layer according to the present invention is controlled between 2.00% and 3.00%.
[0041] In some preferred embodiments, to obtain better technical effects, the mass percentage of Mo is preferably controlled between 2.50% and 3.00%.
[0042] N: In the corrosion-resistant layer according to the present invention, N is a very strong element that forms, stabilizes, and expands the austenite region, and adding an appropriate amount of N can effectively increase the pitting resistance of stainless steel. However, if the nitrogen content is too high, the risk of forming nitrogen-containing intermetallic phases increases, and at the same time, the difficulty of smelting and heat treatment increases, making production difficult. Therefore, in the corrosion-resistant layer according to the present invention, the mass percentage of N is controlled between 0.02% and 0.20%.
[0043] In some preferred embodiments, to obtain better technical effects, the mass percentage of N is preferably controlled between 0.05% and 0.15%.
[0044] Accordingly, it should be noted that while controlling the mass percentage of a single chemical element in the corrosion-preventing layer according to the present invention, it is also desirable to control the elements Cr, Mo, and N to satisfy the following inequality: Cr + 3.3 χ²Mo + 16 χ²N ≥ 25%. Each element in the formula represents the content of the corresponding element as a mass percentage. Through such control, it is possible to further ensure that the corrosion-preventing layer exhibits excellent corrosion resistance in an ozone environment.
[0045] Preferably, the chemical elements of the anti-corrosion layer satisfy at least one of the following in mass percentage:
[0046] C: 0.005-0.030%;
[0047] Si: 0.3-0.6%;
[0048] Mn: 0.5-1.5%;
[0049] Ni: 12.00-14.00%;
[0050] Cr: 16.50-17.50%;
[0051] Mo: 2.50-3.00%;
[0052] N: 0.05-0.15%; and
[0053] Cr+3.3XMo+16XN≥26%.
[0054] Preferably, the unavoidable impurities in the corrosion-preventive layer include S≤0.030%; and P≤0.045%.
[0055] In the corrosion-preventive layer of the tube according to the present invention, P and S are both unavoidable impurity elements, and to ensure the quality of the steel, it is better if the impurity element content of the steel is lower when conditions permit.
[0056] S: In the corrosion-preventing layer according to the present invention, S is a harmful impurity element. Therefore, the mass percentage of S in the corrosion-preventing layer must be strictly controlled to satisfy S≤0.030%. Preferably, the mass percentage of S can be controlled to 0-0.005%.
[0057] P: In the corrosion-preventing layer according to the present invention, P is a harmful impurity element. Therefore, the mass percentage of P in the corrosion-preventing layer must be strictly controlled to satisfy P≤0.045%. Preferably, the mass percentage of P can be controlled to 0-0.035%.
[0058] Preferably, the single-layer anti-corrosion layer has a thickness of 0.5% to 20% of the total thickness of the tube, and the chemical elements of the base layer are as follows in mass percentage:
[0059] C: 0.01-0.20%;
[0060] Si: 0.10-0.50%;
[0061] Mn: 0.50-2.00%;
[0062] Al: 0.02-0.04%;
[0063] Ti: 0.005-0.018%;
[0064] Nb: 0.005-0.020%; and
[0065] N≤0.006%;
[0066] The remainder is Fe and inevitable impurities.
[0067] Preferably, the base layer also comprises at least one of the following:
[0068] 0 <B≤0.0003%;
[0069] 0 <Ni≤0.20%;
[0070] 0 <Cr≤0.20%; 및
[0071] 0 <Mo≤0.10%.
[0072] In the technical solution of the present invention, it is preferable to additionally add B, Ni, Cr, and Mo elements to the base layer to further optimize the quality of the base layer steel.
[0073] Preferably, the chemical elements of the base layer satisfy at least one of the following in mass percentage:
[0074] C: 0.01-0.18%;
[0075] Si: 0.10-0.30%;
[0076] Mn: 0.50-1.50%;
[0077] Al: 0.02-0.03%;
[0078] Ti: 0.005-0.015%; and
[0079] Nb: 0.005-0.015%.
[0080] In the present invention, to ensure good mechanical properties of the tube according to the present invention, the chemical element composition of the base layer carbon steel is selected to ensure both high strength and good processability.
[0081] Therefore, the design principle of each chemical element of the base layer carbon steel in the present invention is as follows.
[0082] C: In the base layer of the present invention, C is an austenite-stabilizing element that acts as a solid solution reinforcing agent in steel, which can significantly increase the strength of the steel. However, it should be noted that the C content of the steel should not be too high. If the C content of the steel is too high, not only are the weldability and toughness of the material unfavorable, but hard phase structures such as pearlite and martensite-austenite islands tend to increase, which negatively affects the corrosion resistance of the steel. Therefore, considering the alignment of strength and toughness of the steel sheet and the corrosion resistance requirements of the carbon steel material, the mass percentage of C in the base layer steel according to the present invention is controlled to be between 0.01% and 0.20%.
[0083] In the present invention, the amount of C added is controlled to 0.01-0.20%, which not only ensures that the steel sheet obtains constant hardness and strength under air cooling conditions after rolling but also prevents a decrease in weldability of the base layer steel. In particular, in the case of a high corrosion-resistant clad sheet (corrosion-resistant layer slab + base layer slab) in which the thickness of the corrosion-resistant layer accounts for 0.5% to 20% of the total thickness, the carbon content of the base layer steel must be controlled within the above range.
[0084] To obtain better technical effects, the mass percentage of C is preferably controlled between 0.01% and 0.18%.
[0085] Si: In the base layer of the present invention, adding Si to the steel can effectively improve the purity and deoxidation of the steel. While Si can act as a solid solution strengthening agent in the steel, Si does not contribute to the weldability of the material. In the present invention, the silicon content of the base layer carbon steel is controlled to 0.5% or less, which does not affect the corrosion resistance of the corrosion-preventing layer, and the base layer carbon steel has good weldability. Therefore, in the base layer according to the present invention, the mass percentage of Si is controlled to be between 0.10% and 0.50%.
[0086] To obtain better technical effects, the mass percentage of Si is preferably controlled between 0.10% and 0.30%.
[0087] Mn: In the base layer according to the present invention, adding an appropriate amount of Mn to the steel can delay pearlite transformation, reduce the critical cooling rate, and improve the hardenability of the steel. At the same time, Mn also has the function of solid solution strengthening and is a major solid solution strengthening element of steel. However, it should be noted that too much Mn should not be added. If the Mn content of the steel is too high, segregation bands and martensite structures are prone to occur, which negatively affect the toughness of the steel, and segregation bands also reduce the corrosion resistance of the steel. The amount of Mn added depends mainly on the strength grade of the steel. Generally, the manganese content of low-carbon microalloy steel does not exceed 2.0%. In this case, the Mn contained in the base layer carbon steel does not have a negative effect on the corrosion-resistant layer. Accordingly, in the base layer according to the present invention, the mass percentage of Mn is controlled to be between 0.50% and 2.00%.
[0088] To obtain better technical effects, the mass percentage of Mn is preferably controlled between 0.50% and 1.50%.
[0089] Al: In the base layer according to the present invention, Al is a strong deoxidizing element. To keep the oxygen content of the steel as low as possible, the mass percentage of Al is controlled between 0.02% and 0.04%. Excess Al after deoxidation combines with N in the steel to form AlN precipitates, which can improve the strength of the steel and refine the austenite grain size of the steel during heat treatment. To obtain better technical effects, the mass percentage of Al is preferably controlled between 0.02% and 0.03%.
[0090] Ti: In the base layer according to the present invention, Ti is a strong carbide-forming element. Adding a small amount of Ti to steel is beneficial for fixing N in the steel, and TiN formed by the combination of Ti and N prevents the matrix austenite grains of the base layer from growing excessively when the base slab is heated, and can refine the original austenite grain size. In addition, Ti can combine with carbon and sulfur in the steel to form TiC, TiS, Ti4C2S2, etc., which may exist in the form of inclusions and secondary phase particles. These Ti carbonitride precipitates can also prevent grain growth in the heat-affected zone during welding and improve the weldability of the base layer carbon steel. Based on this, the mass percentage of Ti in the base layer according to the present invention is controlled to be between 0.005% and 0.018%.
[0091] To obtain better technical effects, the mass percentage of Ti is preferably controlled between 0.005% and 0.015%.
[0092] Nb: In the base layer of the present invention, Nb is a strong carbide-forming element, and a small amount of Nb is added to the steel to increase the recrystallization temperature to match the high final rolling temperature of the clad sheet formed mainly by the base layer slab and the corrosion-resistant layer slab in the subsequent rolling process, so that the grains of the base layer are refined after rolling in the recrystallization and non-recrystallization zones, which is beneficial for improving the low-temperature impact toughness of the base layer. Based on this, in the base layer according to the present invention, the mass percentage of Nb is controlled to be between 0.005% and 0.020%.
[0093] To obtain better technical effects, the mass percentage of Nb is preferably controlled between 0.005% and 0.015%.
[0094] N: In the base layer of the present invention, N can form secondary phase particles together with titanium and aluminum to refine the particles and improve strength. However, if the mass percentage of N is too high, the amount of TiN formed is too large and the particles are too coarse, which affects the plasticity of the cladding substrate of the present invention. Based on this, the mass percentage of N in the base layer according to the present invention is controlled to N≤0.006%.
[0095] B: In the present invention, B can significantly improve the hardenability of steel. When considering air cooling after rolling of a high-corrosion-resistant clad sheet (corrosion-preventive layer slab + base layer slab), it is required to obtain a structure of ferrite + pearlite as much as possible and suppress the formation of bainite, especially in the case of high-corrosion-resistant steel sheets and strips where the thickness of the corrosion-preventive layer is within the range of 0.5% to 5% of the total thickness. Therefore, in the present invention, the amount of B added in the base layer is 0 <B≤0.0003%를 만족하도록 제어하는 것이 요구된다.
[0096] Ni: In the present invention, Ni is an element that stabilizes austenite and plays a role in improving the strength of steel. In addition, adding an appropriate amount of Ni, particularly to quenched and tempered steel, can significantly improve the low-temperature impact toughness of the steel. Based on this, an appropriate amount of Ni can be added to the base layer according to the present invention, and the amount of Ni added is 0 <Ni≤0.20%를 만족하도록 제어한다.
[0097] Cr: In the present invention, the segregation tendency of Cr is smaller than that of Mn. When the Mn content of the base layer carbon steel is high and there are distinct segregation zones and band-like structures in the steel, the Mn content can be appropriately reduced, and the deficient portion can be replaced with Cr. Second, adding an appropriate amount of Cr to the matrix carbon steel is also beneficial in suppressing the diffusion of Cr from the corrosion-preventive layer into the base layer. Based on this, in the base layer according to the present invention, 0 <Cr≤0.20%를 만족하는 Cr을 첨가할 수 있다.
[0098] Mo: In the present invention, Mo can significantly refine the grain size and improve the strength and toughness of the steel. Additionally, Mo can reduce the tempering brittleness of the steel, and at the same time, very fine carbides can be precipitated during tempering, thereby significantly strengthening the steel matrix. Furthermore, the addition of Mo contributes to suppressing self-tempering brittleness that easily forms in steel sheets during air cooling. Based on this, an appropriate amount of Mo can be added to the base layer according to the present invention, and the amount of Mo added is 0 <Mo≤0.10%를 만족하도록 제어한다.
[0099] Preferably, the unavoidable impurities in the base layer include S≤0.010%; and P≤0.015%.
[0100] In the technical solution of the present invention, both P and S belong to the unavoidable impurity elements of the base layer, and S will combine with Mn in the steel to form plastic inclusions of manganese sulfide, which is particularly detrimental to the transverse plasticity and toughness of the steel; therefore, the S content of the base layer must be as low as possible. In addition, P is also a harmful element in steel, which will seriously impair the plasticity and toughness of the steel sheet.
[0101] In the case of the present invention, since both S and P are unavoidable impurity elements, it is better if their content is lower. Considering the actual steelmaking level of a steel mill, S and P in the base layer of the present invention are controlled to satisfy S ≤ 0.010%; and P ≤ 0.015%.
[0102] Preferably, the single-layer anti-corrosion layer has a thickness of 0.5% to 20% of the total thickness of the tube.
[0103] In the present invention, depending on the operating conditions, the selection of the thickness of the corrosion-resistant layer plays a decisive role in obtaining good corrosion resistance, mechanical properties, and formability of the tube. If the corrosion-resistant layer is too thick, it affects the mechanical properties and production costs of the material, whereas if the corrosion-resistant layer is too thin, the corrosion resistance and service life of the material are reduced. For this reason, in the present invention, the corrosion-resistant layer has a controlled thickness that preferably accounts for 0.5% to 20% of the total thickness of the clad slab, and more preferably 2.5% to 10% of the total thickness of the tube.
[0104] Preferably, the base layer has a microstructure of ferrite + pearlite or ferrite + pearlite + bainite; and the corrosion-resistant layer has a microstructure of austenite.
[0105] Preferably, the tube has a yield strength ≥435 MPa, a tensile strength ≥590 MPa, an elongation ≥30%, and a uniform corrosion rate of the anti-corrosion layer in an ozone environment ≤0.05 mm / year.
[0106] Accordingly, another objective of the present invention is to provide a method for manufacturing the aforementioned tube, which is simple and feasible, and can effectively manufacture the aforementioned tube, and can break the thickness limitation of the corrosion-resistant layer and control the thickness of the corrosion-resistant layer to within the range of 0.5% to 20% of the total thickness of the tube.
[0107] To achieve the above objective, the present invention provides a method for manufacturing the aforementioned tube, comprising the following steps:
[0108] (1) Step of preparing a corrosion-resistant layer slab and a base layer slab;
[0109] (2) A step of assembling the corrosion-resistant layer slab and the base layer slab to obtain a clad slab, wherein the single-layer corrosion-resistant layer preferably has a thickness of 0.5% to 20% of the total thickness of the clad slab, more preferably 2.5% to 10% of the total thickness of the clad slab;
[0110] (3) A step of heating and rolling, wherein the clad slab is heated at a temperature of 1100 to 1200°C, and then multi-pass rolling is performed, wherein the total reduction rate is 90% or more, and the final rolling is performed at a temperature of 900°C or higher;
[0111] (4) As a coiling step, after water cooling, a step of controlling the coiling into a hot-rolled coil at a temperature of 500~650℃;
[0112] (5) A step of performing surface treatment on the hot-rolled coil; and
[0113] (6) Tube manufacturing step.
[0114] In the present invention, the inventors designed a new manufacturing method optimized through extensive research based on the rational design of the chemical composition, and an ozone corrosion-resistant high-strength tube can be effectively manufactured by this method.
[0115] In the manufacturing method according to the present invention, the corrosion-resistant layer slab and the base layer slab may be manufactured by smelting and casting according to the chemical composition design, and then the corrosion-resistant layer slab and the base layer slab are assembled to obtain a high-corrosion-resistant clad sheet (corrosion-resistant layer sheet + base layer sheet). Then, the obtained high-corrosion-resistant clad sheet is heated, rolled, and coiled to obtain a hot-rolled coil having a clad intermediate layer structure, and then the hot-rolled coil is surface-treated and tube fabrication is performed to obtain a tube according to the present invention.
[0116] In the present invention, the inventors design the heating and rolling process of step (3) in an optimized manner to ensure that a transition layer structure of a certain thickness is formed between the corrosion-resistant layer and the base layer of the high-corrosion-resistant clad sheet through processes such as heating and rolling, and to realize a complete metallurgical bond between the corrosion-resistant layer and the base layer, thereby improving the applicability and economic efficiency of the material while ensuring ozone corrosion resistance and mechanical properties.
[0117] In step (2) of the manufacturing method according to the present invention, the manufactured corrosion-resistant layer slab and base layer slab are pretreated, the periphery of the joint surface of the slab is welded and sealed, and the welded and sealed joint surface is vacuum-treated to complete the assembly of the slab.
[0118] Accordingly, in step (5), the hot-rolled coil undergoes surface treatment, which can be achieved through acid pickling or mechanical descaling. Additionally, in the tube manufacturing process of step (6), a conventional spiral welding method or a longitudinal welding method may be adopted for forming and welding. The welding method may be selected from submerged arc welding, metal gas arc welding, tungsten inert gas welding, plasma arc welding, electrode arc welding, high-frequency welding, or laser welding.
[0119] Preferably, in the manufacturing method according to the present invention, in step (3), the temperature at which the final rolling is performed is controlled to 920 to 1000°C.
[0120] Preferably, in the manufacturing method according to the present invention, a preheating step is additionally included between step (2) and step (3), wherein the preheating is performed at a temperature of 1150 to 1250°C.
[0121] In the manufacturing method according to the present invention, depending on the performance requirements of the finished product, it may also be determined whether to perform a preheating process between step (2) and step (3). In the preheating process, the clad slab obtained by assembling the slab can be heated at a temperature of 1150 to 1250°C, so that a uniform austenite structure can be obtained in the corrosion-resistant layer on the surface of the clad slab, and the previously possible carbides can be dissolved as completely as possible, and at the same time, compounds of alloying elements such as niobium and titanium in the carbon steel can be completely or partially dissolved; and the elements of the corrosion-resistant layer and the carbon steel base layer diffuse at the interface to form a stable transition layer and then slowly cool to room temperature.
[0122] Preferably, in the manufacturing method according to the present invention, cold rolling and annealing are additionally included between step (5) and step (6).
[0123] In the manufacturing method according to the present invention, if the target product before tube production is a cold-rolled coil rather than a hot-rolled coil for actual use, a cold rolling and annealing step may be additionally added between step (5) and step (6), which can be achieved by cold rolling to a target thickness and annealing. Preferably, annealing is performed at a temperature of 900 to 1000°C.
[0124] Therefore, in the present invention, an ozone-resistant corrosion-resistant layer is formed on the surface of the base layer of a carbon steel plate through rolling processing by designing the composition and ratio of the ozone-resistant corrosion-resistant layer and the base layer. Finally, a sheet / strip having ozone resistance, good mechanical properties, and high economic efficiency is formed, and this is further processed to manufacture it into a tube shape for use in pipelines and equipment of water supply facilities in ozone-corrosive media environments.
[0125] The design difficulties of the present invention are as follows.
[0126] 1) The compositional design of the corrosion protection layer and the base layer must satisfy the overall characteristics of the material. The composition of the corrosion protection layer must be designed according to the characteristics of ozone corrosion to meet the corrosion resistance requirements under operating conditions. In the case of designing the carbon steel composition of the base layer, in addition to meeting the mechanical property requirements, it must also be considered that when the carbon content of the transition layer is high at the junction of the corrosion protection layer and the base layer, there is a lack of stabilizing elements, a clear decarburization layer is present on one side of the carbon steel at the interfacial junction, and the structure of the carbon steel substrate is uneven, surface defects are likely to occur after processing, and mechanical properties may not meet the standards.
[0127] 2) It is difficult to control the heating, rolling, and heat treatment processes due to differences in the ratio of the corrosion-resistant layer to the matrix metal and material properties. For example, if the temperature is uneven during the heating process, deformation and expansion occur, making it impossible to bond with the base layer. For instance, there is a high probability of separation from the matrix and cracking during rolling, and it is difficult to guarantee thickness uniformity.
[0128] 3) For pipelines and equipment used in water supply facilities in ozone-corrosive media environments, such as ozone generators, ozone dosing devices, and pipelines between pre-ozone contact tanks and water discharge pipes of ozone contact tanks, if the initial cladding is not completed and the bonding quality is poor, the continuity and uniformity of the anti-corrosion layer on the finished product cannot be guaranteed after subsequent processing steps such as acid cleaning, tube fabrication and forming, and welding. This poses a significant risk to the applicability, safety, and durability of the equipment and pipelines.
[0129] In the present invention, the inventors successfully overcame the above difficulties through a reasonable design and manufactured and obtained an ozone corrosion-resistant high-strength tube according to the present invention. Effects of the invention
[0130] Compared to conventional technology, the ozone corrosion-resistant high-strength tube according to the present invention and the method for manufacturing the same exhibited the following advantages and beneficial effects.
[0131] In the present invention, the inventors consider the operating conditions of pipelines and equipment currently used in water supply facilities in ozone-corrosive media environments. By designing the composition and ratio of the corrosion-resistant layer and the base layer, the corrosion-resistant layer and the base layer are combined and assembled, and a tube is obtained having ozone corrosion resistance, excellent mechanical properties, and high economic efficiency through appropriate heating, rolling, and coiling processes and a tube manufacturing process. The tube has a yield strength ≥435 MPa, a tensile strength ≥590 MPa, an elongation ≥30%, and a uniform corrosion rate of the corrosion-resistant layer in an ozone environment ≤0.05 mm / year.
[0132] In the present invention, a transition layer structure of a certain thickness is formed between the corrosion-preventing layer and the base layer through processes such as heating and rolling, and by realizing complete metallurgical bonding between the corrosion-preventing layer and the base layer, the applicability and economic efficiency of the material are improved, and ozone corrosion resistance and mechanical properties are secured.
[0133] Using tubes manufactured through the above configuration design and process control methods can solve the essential problems associated with 316 stainless steel or carbon steel used in water supply facilities in ozone-corrosive media environments. These tubes can be used as pipelines and equipment in water supply facilities in ozone-corrosive media environments, such as pipelines between ozone generators and ozone dosing devices, and as discharge pipes between pre-ozone contact tanks and ozone contact tanks. They can meet the requirements for ozone corrosion prevention and mechanical properties of such pipelines and equipment, significantly improve the applicability, safety, and durability of these pipelines and equipment, and simultaneously prevent secondary water contamination, thereby demonstrating significant economic and social benefits.
[0134] Compared to 316 stainless steel tubes used as pipelines between ozone generators and ozone dosing devices in water supply facilities, and as discharge pipes for pre-ozone contact tanks and ozone contact tanks, the tube according to the present invention exhibits higher strength, simpler welding and processing, better corrosion resistance, and higher economic efficiency. Compared to carbon steel tubes used as water discharge pipes behind valves of pre-ozone contact tanks and ozone contact tanks, the tube according to the present invention allows for the omission of the process of applying a corrosion-resistant coating to the tube, exhibits corrosion resistance and durability incomparable to carbon steel tubes, is more energy-efficient, environmentally friendly, and requires no maintenance. Brief explanation of the drawing
[0135] FIG. 1 is a schematic diagram of an intermediate layer structure of a tube according to one embodiment of the present invention. FIG. 2 is a schematic diagram of an intermediate layer structure of a tube according to another embodiment of the present invention. Figure 3 is a photograph of the microstructure of the bonding interface between the base layer and the anti-corrosion layer of the tube in Example 5. Figure 4 is a photograph of the microstructure of the base layer of the tube in Example 5. Specific details for implementing the invention
[0136] A tube according to the present invention and a method for manufacturing the same will be further described and illustrated with reference to the accompanying drawings and specific embodiments, but this is not intended to unduly limit the technical solution of the present invention.
[0137] Examples 1 to 6 and Comparative Example 1
[0138] Table 1 lists the chemical elements in mass percentages in the corrosion-resistant layer of the tubes of Examples 1 to 6 and Comparative Example 1.
[0139] [Table 1] (Wet%, remainder is unavoidable impurities other than Fe, P, and S)
[0140]
[0141] Note: In Table 1 above, each element in the formula Cr+3.3KMo+16KN represents the mass percentage of the corresponding element.
[0142] Table 2 lists the chemical elements of the tube base layers of Examples 1 to 6 and Comparative Example 1 in mass percentage.
[0143] [Table 2] (Wet%, remainder is unavoidable impurities other than Fe, P, and S)
[0144]
[0145] The tubes of Examples 1 to 6 and Comparative Example 1 of the present invention were manufactured according to the following steps.
[0146] (1) Smelting and casting were performed to manufacture corrosion-resistant layer slabs and base layer slabs, respectively, according to the chemical compositions shown in Table 1 and Table 2.
[0147] (2) A clad slab was obtained by assembling a corrosion-resistant layer slab and a base layer slab. The thickness of the corrosion-resistant layer was adjusted to 0.5% to 20% of the total thickness of the clad slab, and pretreatment was performed on the corrosion-resistant layer slab and the base layer slab. The area around the slab joint surface was welded and sealed, and the welded and sealed joint surface was vacuum-treated. Whether to perform a preheating process was determined based on the performance requirements of the finished product after assembling the slabs, and if preheating was required, the preheating temperature was adjusted to 1150~1250℃.
[0148] (3) Heating and rolling: After heating the clad slab at a temperature of 1100 to 1200°C, multi-pass rolling is performed within the temperature range of austenite recrystallization and non-recrystallization of the base layer slab and the corrosion-resistant layer slab, the total reduction rate is controlled to be 90% or more, and final rolling is performed at a temperature of 900°C or higher, preferably at a temperature of 920 to 1000°C.
[0149] (4) Coiling: After water cooling, hot-rolled coils are manufactured by controlling the coiling to be performed at a temperature of 500 to 650°C.
[0150] (5) Surface treatment is performed on the hot-rolled coil by adopting pickling or mechanical descaling. If the target product is a cold-rolled coil, additional cold rolling and annealing processes are performed, and then the coil is annealed after cold rolling to achieve the target thickness.
[0151] (6) Tube fabrication: Forming and welding were performed using a spiral welding method or a longitudinal welding method, and the tube was fabricated using a selected welding method among submerged arc welding, metal gas arc welding, tungsten inert gas welding, plasma arc welding, welding rod arc welding, high frequency welding or laser welding.
[0152] In the present invention, it should be noted that the tubes of Examples 1 to 6 of the present invention were all manufactured using the process of steps (1)-(6), and that the chemical composition and related process parameters all satisfy the control requirements of the design specifications of the present invention.
[0153] Table 3 lists the specific process parameters of the tubes of Examples 1 to 6 and Comparative Example 1 in the steps of the manufacturing method described above.
[0154] [Table 3]
[0155]
[0156] It should be noted that according to the process parameters shown in Table 3 above, cold rolling and annealing were additionally performed after step (5) of performing surface treatment on the hot-rolled coil in Examples 1 and 3 to obtain a cold-rolled sheet, and hot-rolled sheets were obtained after step (5) in Examples 2, 4, 5, 6 and Comparative Example 1.
[0157] Accordingly, the sheets manufactured according to the examples and comparative examples can be additionally used to manufacture the corresponding tubes in the tube manufacturing process of step (6).
[0158] Tubes of Examples 1 to 6 and Comparative Example 1 manufactured using the above process were each sampled, and the microstructure of the sample tubes of Examples 1 to 6 and Comparative Example 1 was further observed. After observing the microstructure of the tubes, mechanical property tests and ozone corrosion resistance tests were further performed on the sample tubes of Examples 1 to 6 and Comparative Example 1, and the test results are shown in Table 4 below.
[0159] The relevant performance test methods are as follows.
[0160] Mechanical properties test: GB / T 6396-2008 Clad steel plate - Mechanical and technical test( Clad Steel Plates-Mechanical and Technological TestYield strength, tensile strength, and elongation of the sample tubes of Examples 1 to 6 and Comparative Example 1 were obtained according to ).
[0161] Ozone Corrosion Resistance Test: Using the "Coupon Test Method for Specific Application Scenarios," test coupons were inserted into the water discharge pipe of a pre-ozone contact tank in a water supply facility. After three months, the test coupons were removed, and the surface condition of the anti-corrosion layer was observed to check for corrosion, thereby obtaining the ozone corrosion resistance of the sample tubes of Examples 1 to 6 and Comparative Example 1.
[0162] Table 4 shows the test results for the microstructure, mechanical properties, and ozone corrosion resistance of the tubes of Examples 1 to 6 and Comparative Example 1.
[0163] [Table 4]
[0164]
[0165] As shown in Table 4 above, the tubes of Examples 1 to 6 of the present invention have a yield strength of 435 MPa to 516 MPa, a tensile strength of 590 MPa to 650 MPa, and an elongation of 30.0% to 40.0%, and exhibit excellent ozone corrosion resistance, and the corrosion resistance layer did not corrode in an ozone environment after 3 months, whereas the final corrosion layer of Comparative Example 1 was slightly corroded because the composition design of the corrosion resistance layer did not meet the design requirements of the present invention.
[0166] As can be seen in the above examples, tubes with excellent mechanical properties and ozone corrosion resistance can be obtained through appropriate material selection, structural design, rolling and heat treatment processes, and tube fabrication. This can solve the inherent problems of 316 stainless steel or carbon steel currently used in water supply facilities in ozone-corrosive media environments, meet the increasing demand for corrosion resistance and mechanical properties for pipelines and equipment used in water supply facilities in ozone-corrosive media environments, and obtain significant economic and social benefits.
[0167] FIG. 1 is a schematic diagram of an intermediate layer structure of a tube according to one embodiment of the present invention.
[0168] As shown in FIG. 1, in this embodiment, the tube according to the present invention may include two corrosion-resistant layers located on the inner and outer surfaces of the tube and a base layer located between the two corrosion-resistant layers.
[0169] FIG. 2 is a schematic diagram of an intermediate layer structure of a tube according to another embodiment of the present invention.
[0170] As shown in FIG. 2, in this embodiment, the tube according to the present invention may include a corrosion-resistant layer located on the inner surface of the tube and a base layer located on the outer surface of the tube.
[0171] Figure 3 is a photograph of the microstructure of the bonding interface between the base layer and the anti-corrosion layer of the tube in Example 5.
[0172] As shown in Fig. 3, in Example 5, the microstructure of the base layer of the tube was ferrite-pearlite-bainite. The microstructure of the corrosion-resistant layer was austenite. Accordingly, the elements of the corrosion-resistant layer and the base layer diffused at the bonding interface to form a stable transition layer with a diffusion distance of 50 to 100 μm.
[0173] Figure 4 is a photograph of the microstructure of the tube base layer of Example 5.
[0174] As shown in Fig. 4, the microstructure of the tube base layer in Example 5 was ferrite-pearlite-bainite.
[0175] The prior art portion within the scope of protection of the present invention is not limited to the examples given in the documentation of the present invention, and all prior art that does not contradict the solution of the present invention, including but not limited to prior patent documents, prior disclosures, and the use of prior disclosures, may be included within the scope of protection of the present invention. Furthermore, the combination of features of the present invention is not limited to the combinations described in the claims or specific embodiments, and all features described in the present invention may be freely combined or combined in any way, provided that they do not contradict one another.
[0176] Furthermore, it should be noted that the embodiments listed above are merely specific embodiments of the present invention. Clearly, the present invention is not limited to the above embodiments, and similar modifications or variations made accordingly can be directly derived or readily conceived by those skilled in the art from the disclosure of the present invention, and all fall within the scope of protection of the present invention.
Claims
Claim 1 As a tube, the tube has a corrosion-resistant layer and a base layer in the thickness direction, the corrosion-resistant layer is located at least on the inner wall of the tube, and the corrosion-resistant layer contains the following chemical element in mass percentage, 0 <C≤0.08%;0<Si≤0.75%;0<Mn≤2.0%;Ni: 10.00-14.00%;Cr: 16.00-18.00%;Mo: 2.00-3.00%; 및N: 0.02-0.20%,나머지는 Fe 및 불가피한 불순물이고, 여기서 Cr, Mo 및 N의 질량 백분율은 다음의 부등식을 만족하고: Cr+3.3ХMo+16ХN≥25%,상기 기저층의 화학 원소는 질량 백분율로 다음의 화학 원소를 함유하며:C: 0.01-0.20%;Si: 0.10-0.50%;Mn: 0.50-2.00%;Al: 0.02-0.04%;Ti: 0.005-0.018%;Nb: 0.005-0.020%; 및N≤0.006%,나머지는 Fe와 불가피한 불순물이고,상기 기저층은 페라이트(ferrite) + 펄라이트(pearlite) 또는 페라이트 + 펄라이트 + 베이나이트(bainite)의 미세 구조를 갖고; 상기 부식 방지층은 오스테나이트(austenite)의 미세 구조를 갖는 것을 특징으로 하는 튜브. Claim 2 The tube according to claim 1, characterized in that the chemical elements of the corrosion-preventing layer satisfy one or more of the following in mass percentage: C: 0.005-0.03%; Si: 0.3-0.6%; Mn: 0.5-1.5%; Ni: 12.00-14.00%; Cr: 16.50-17.50%; Mo: 2.50-3.00%; and N: 0.05-0.15%, where the mass percentages of Cr, Mo and N satisfy the following inequality: Cr + 3.3^(Mo) + 16^(N) ≥ 26%. Claim 3 delete Claim 4 A tube according to claim 1 or 2, characterized in that the unavoidable impurities in the corrosion-preventing layer are S≤0.030%; and P≤0.045%. Claim 5 A tube according to claim 1 or 2, characterized in that the single-layer corrosion-resistant layer has a thickness of 0.5% to 20% of the total thickness of the tube. Claim 6 In claim 1, the base layer further comprises at least one of the following tubes: 0 <B≤0.0003%;0<Ni≤0.20%;0<Cr≤0.20%; 및0<Mo≤0.10%. Claim 7 The tube according to claim 1, characterized in that the chemical elements of the base layer satisfy at least one of the following in mass percentage: C: 0.01-0.18%; Si: 0.10-0.30%; Mn: 0.50-1.50%; Al: 0.02-0.03%; Ti: 0.005-0.015%; and Nb: 0.005-0.015%. Claim 8 A tube according to claim 1, wherein the unavoidable impurities in the base layer include S≤0.010%; and P≤0.015%. Claim 9 delete Claim 10 delete Claim 11 A tube according to claim 1 or 2, characterized in that the tube has a yield strength ≥435 MPa, a tensile strength ≥590 MPa, and an elongation rate ≥30%, and the corrosion-preventing layer does not exhibit corrosion on its surface even after being placed in an ozone environment. Claim 12 A method for manufacturing a tube according to claim 1 or 2, comprising the following steps: (1) preparing a corrosion-resistant layer slab and a base layer slab; (2) assembling the corrosion-resistant layer slab and the base layer slab to obtain a clad slab, wherein the single-layer corrosion-resistant layer has a thickness that occupies 0.5% to 20% of the total thickness of the clad slab; (3) a heating and rolling step, wherein the clad slab is heated at a temperature of 1100 to 1200°C and then subjected to multi-pass rolling, wherein the total reduction ratio is 90% or more and the final rolling is performed at a temperature of 900°C or higher; (4) a coiling step, wherein, after water cooling, the coiling is controlled into a hot-rolled coil at a temperature of 500 to 650°C; (5) a surface treatment is performed on the hot-rolled coil. and (6) tube manufacturing step. Claim 13 A method according to claim 12, characterized in that the final rolling in step (3) above is carried out at a temperature of 920 to 1000°C. Claim 14 In claim 12, the method further comprises a preheating step between step (2) and step (3), and the preheating is performed at a temperature of 1150 to 1250°C. Claim 15 In claim 12, the method further comprises cold rolling and annealing between step (5) and step (6), and the annealing is performed at a temperature of 900 to 1000°C.
Citation Information
Patent Citations
Stainless steel member having crevice structure
JP2007217776A
Carbon steel and austenitic stainless steel rolling clad plate and manufacturing method therefor
WO2021104417A1
Electrode-welded clad steel pipe and its manufacturing method
KR1020190051033A
